The Utilization Of Artificial Intelligence As An Innovative Solution In Monitoring Mining Activities And Combating Illegal Mining (PETI) - Safriansyah Yanwar Rosyadi; Ahmad Redi (PT. ALHAFI BERKAH INDONESIA, 2025)
Illegal Mining (Penambangan Tanpa Izin/PETI) is a serious problem causing significant negative impacts on the environment, society, and economy in Indonesia. Conventional monitoring systems used so far face various limitations, such as a lack of human resources, infrastructure, and adequate technology, making the supervision and control of PETI less effective. This article examines the potential utilization of Artificial Intelligence (AI) technology as an innovative solution to improve the effectiveness of monitoring PETI activities. By leveraging AI, monitoring can be conducted in real-time, with accuracy, and across wide areas through the integration of satellite imagery, drones, and IoT sensors. However, the implementation of AI also faces challenges such as limited human resources, infrastructure, data security issues, and insufficient regulations. Therefore, this study recommends collaboration among government agencies, the private sector, and academia, capacity building for human resources, and the formulation of adaptive regulations as strategic steps to optimize the use of AI in monitoring and combating PETI in Indonesia. The findings of this study are expected to serve as a reference for policymakers and practitioners in integrating advanced technology to safeguard the sustainability of natural resources.